Impact of process flexibility and imperfect forecasting on the operation and design of Haber–Bosch green ammonia - Salmon, N; Bañares-Alcántara, R (Royal Society of Chemistry, 2023)
Green ammonia is a promising energy storage vector which can provide back-up power when variable renewable energy sources (VREs) are not generating. However, it is generally agreed in the literature that the limited flexibility of the Haber-Bosch process required for ammonia synthesis increases its production cost. We assess the truth of this claim using two methods: firstly, a perfect forecasting design model based on Linear Programming (LP); and secondly, a model predictive control (MPC) approach which can estimate how the plant will operate with finite weather forecast information. This MPC approach is the first in the literature to demonstrate how islanded green ammonia plants can be operated without perfect forecasting. The LP approach demonstrates that, from a design perspective, there are diminishing marginal returns from improving HB flexibility; by 2050, there will be almost no benefit associated with reducing the HB MOR below 60%. The MPC approach supports this claim at a solar-dominated sites; however, at wind-dominated sites, the inability to perform long-distance forecasting means flexibility is an important lever for the plant to operate robustly.